The HCR-20 Violence Risk Assessment Scheme - Douglas, Kevin S. (Criminal justice and behavior, 1999)
The Historical, Clinical, and Risk Management (HCR-20) violence risk assessment scheme was coded in a sample of 75 Canadian male, federally sentenced, maximum-security offenders. The concurrent validity of the HCR-20 was assessed through comparison to other risk instruments and to the presence of several past indexes of violent and antisocial behavior. The HCR-20 showed moderate to strong relationships with the concurrent measures. The HCR-20 was as or more strongly related to past violence than were the Psychopathy ChecklistΓÇöRevised or the Violence Risk Appraisal Guide. Scores above the median of the HCR-20 increased the odds of the presence of various measures of past violence and antisocial behavior by an average of four times. Although recognizing the limitations of a small sample and retrospective design, the results give some indication that the HCR-20 may be worth investigating as a useful tool for violence risk assessments in correctional samples